2005
DOI: 10.1111/j.1523-1755.2005.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of soluble guanylate cyclase slows progression in anti-thy1-induced chronic glomerulosclerosis

Abstract: Glomerular and tubulointerstitial soluble guanylate cyclase activity are discordantly altered in anti-thy1-induced chronic glomerulosclerosis. Stimulation of soluble guanylate cyclase signaling by Bay 41-2272 limits the progressive course of this model toward tubulointerstitial fibrosis and impaired renal function at least in part in a blood pressure-independent manner. The results suggest that soluble guanylate cyclase activation counteracts fibrosis and progression in chronic renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…The mAb 1-22-3 antibody binds to a thy1-like antigen on the surface of mesangial cells of the kidney and causes a fast complement-dependent and NO-dependent mesangial cell lysis within the next 24 h (17,27). The progression in cGS is linked to the uninephrectomy that is performed before anti-thy1 antibody injection, since the glomerular disease resolves over ϳ4 wk in animals with two kidneys (17,21,27). Control animals were injected with equal volumes of PBS only.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mAb 1-22-3 antibody binds to a thy1-like antigen on the surface of mesangial cells of the kidney and causes a fast complement-dependent and NO-dependent mesangial cell lysis within the next 24 h (17,27). The progression in cGS is linked to the uninephrectomy that is performed before anti-thy1 antibody injection, since the glomerular disease resolves over ϳ4 wk in animals with two kidneys (17,21,27). Control animals were injected with equal volumes of PBS only.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic-progressive glomerulosclerosis (cGS) was produced by surgically removing one kidney and intravenously injecting the monoclonal antibody mAb 1-22-3 (5 mg/kg body wt in PBS, pH ϭ 7.4) 3 days later (17,21,27). The mAb 1-22-3 antibody binds to a thy1-like antigen on the surface of mesangial cells of the kidney and causes a fast complement-dependent and NO-dependent mesangial cell lysis within the next 24 h (17,27). The progression in cGS is linked to the uninephrectomy that is performed before anti-thy1 antibody injection, since the glomerular disease resolves over ϳ4 wk in animals with two kidneys (17,21,27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Recent pharmacologic studies suggested that soluble GC are involved in a chronic model of glomerulonephritis 7,8 ; however, little is known about the role of receptor GC in renal diseases.…”
mentioning
confidence: 99%
“…Several studies have shown that enhanced NO availability improves the clinical course of anti-Thy1-glomerulonephritis (17,28), presumably via stimulation of endothelial NO synthase (eNOS). Consistently, enhancement of NO-stimulated cGMP production by soluble guanylate cyclase slows progression of anti-Thy1-glomerulonephritis (32). Rosiglitazone has been shown to enhance NO production by increasing eNOS transcription in isolated endothelial cells and eNOS phosphorylation in mice hearts (6) and isolated endothelial cells (20).…”
Section: Ajp-renal Physiolmentioning
confidence: 81%